Analisis Sandi Algoritma Enkripsi Substitusi permutasi 4 Ronde - Yusuf Kurniawan (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Encryption is one of the most important components in security of application ofinformation technology. We need the good knowledge of encryption attack, to create thestrong, rapid, and flexible encryption algorithm. This research shows that security ofencryption algorithm does not only depend on the bits number of key, but also depend on thestructure of algorithm itself. The more complicated the algorithm is (it is hoped more secure)the slower the algorithm runs, so the algorithm is not comfortable to be used. This researchincludes cryptanalysis and programming to attack the algorithm of simple encryption, 80-bitkey, which can be broken theoretically in 19 years using 1 million computers, with brute forceattack. In this research, this algorithm can be broken less than one minute with 10 thousandcharacters of known plain text with one personal computer, although the algorithm has goodstatistical property.Keywords: encryption, cryptanalysis, brute force attack, statistical property, known plaintext